2016
DOI: 10.1111/tra.12404
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Disease Pathogenesis Differ in Krabbe Disease Variants

Abstract: Krabbe disease is a severe, fatal neurodegenerative disorder caused by defects in the lysosomal enzyme galactocerebrosidase (GALC). The correct targeting of GALC to the lysosome is essential for the degradation of glycosphingolipids including the primary lipid component of myelin. Over 100 different mutations have been identified in GALC that cause Krabbe disease but the mechanisms by which they cause disease remain unclear. We have generated monoclonal antibodies against full‐length human GALC and used these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…Moreover, the GALC D528N mutant was found to be hyperglycosylated and misfolded and its function can be partially rescued by a treatment with the pharmacological chaperone α-lobeline (Lee et al, 2010). Another study confirmed that many GALC mutants were trapped within the ER instead of reaching the lysosome (Spratley et al, 2016). These data suggest that failure of ERQC is an important determinant in KD pathogenesis.…”
Section: Er Protein Quality Control and Myelin Diseases Of The Cnsmentioning
confidence: 77%
“…Moreover, the GALC D528N mutant was found to be hyperglycosylated and misfolded and its function can be partially rescued by a treatment with the pharmacological chaperone α-lobeline (Lee et al, 2010). Another study confirmed that many GALC mutants were trapped within the ER instead of reaching the lysosome (Spratley et al, 2016). These data suggest that failure of ERQC is an important determinant in KD pathogenesis.…”
Section: Er Protein Quality Control and Myelin Diseases Of The Cnsmentioning
confidence: 77%
“…The G270D mutation, commonly associated with late-onset forms of the disease, is often found alongside the common polymorphism I546T (found in 35-45% of the population); together, they show lower GALC activity than when expressed on their own . Likewise, it has been shown by Shin et al (2016) and Spratley et al (2016) that the combination of certain cispolymorphisms and disease mutations can significantly reduce the activity and trafficking of GALC. The full impact of known polymorphisms on KD prognosis and therapeutic intervention has yet to be elucidated but must be taken into consideration when characterizing and identifying candidate GALC mutations.…”
Section: Identifying Candidatementioning
confidence: 96%
“…Missense mutations that lie within the active site of GALC, such as the R380W mutation (Fig. 4), directly disrupt the interactions between enzyme and substrate, critically affecting enzyme activity but not folding (Hill et al, 2013;Spratley, et al, 2016). The R380W mutation thus causes a severe, early-onset form of KD because of catalytic inactivity (Wenger et al, 1997).…”
Section: Identifying Candidatementioning
confidence: 99%
“…A limitation of this approach is that it is not able to provide information on other types of mutations known to give rise to enzyme deficiencies. Examples of these include splicing mutations such as the aforementioned E8SJM/c.894G>A pathogenic mutation found in the majority of patients with CA‐LALD (Bernstein et al, ; Scott et al, ) as well as mutations that inhibit trafficking beyond the endoplasmic reticulum and trans‐Golgi network as has been observed in other lysosomal storage diseases (Parenti et al, ; Ron & Horowitz, ; Spratley et al, ; Zhang et al, ). Another potential limitation of our analysis is the use of the artificial 4‐MU oleate substrate rather than naturally occurring substrates such as cholesteryl esters or triglycerides.…”
Section: Discussionmentioning
confidence: 99%